O MODELO SOCIAL DA DEFICIÊNCIA NO DIREITO BRASILEIRO: Reconhecimento, Justiça e Direitos Humanos - CHAVES, Denisson Gonçalves (2017)
Nowadays, the deficiency is a multidimensional thematic, approached by the most various areas of the Science, from the spheres of health, like medicine, to Social Sciences, such as Law and Politics. However, this plurivision is something recent, so that until the middle of the 21st century a purely biomedical perspective of the phenomenon of disability prevailed in a hegemonic way, considering it as pathology. The social model of disability emerges as an innovative paradigm, defining disability as the livingness in bodies with impairments in environments with barriers. In these terms, it becomes part of human diversity, not a stigma. In spite of this interpretative revolution, the deficiency is still governed by common standards, by charitable attitudes or even relegated to social invisibility. The Brazilian Law contains a vast number of protective norms for people with disabilities, however, they need enforcement. This misfortune is due in part to the lack of studies on this topic from a legal perspective. Furthermore, even within the sociology of health, the social model is still poorly diffused. Therefore, the objective of this work is to analyze the social model of disability from a Law perspective, showing "if" and "how" the internal legal system is adopting such archetype. The methodology used was the analysis of the content of national and international decisions and legislations, as well as the bibliographic review about the disability. The results found in this study show that the Brazilian State has a mechanism to enforce the rights of people with functional diversity, though, obstacles, such as invisibility, prejudice and socioinstitutional disengagement represent environmental barriers that generate and promote the exclusion of the disabled.